From Formal Rights to Substantive Justice: Rethinking Legal Protection for Divorced Women in Indonesia - Patawari, A. Muh Yusri; Jafar, Usman; Supardin; Asni; Andi Kitta, Andi Abdul Kadir (Universitas Islam Negeri Alauddin Makassar, 2026)
This study examines the effectiveness of legal protection for women victims of domestic violence after divorce and formulates strategies to strengthen substantive justice. Using an empirical juridical approach, the research employed statutory, case, and conceptual analyses. Primary data were collected through interviews with religious court judges, court clerks, advocates, and victims of domestic violence, supported by courtroom observations, while secondary data were derived from legislation, court decisions, Badilag documents, and relevant literature. The findings reveal that legal protection remains ineffective due to weak implementation structures, limited victim-centered perspectives among legal officials, and persistent legal cultures that treat domestic violence as a private matter. The study further finds that religious courts have not fully integrated gender-sensitive and recovery-oriented approaches into post-divorce dispute resolution. To address these challenges, the research proposes strengthening victim-oriented regulations, improving judicial capacity through gender justice training, expanding access to legal aid services, and promoting women’s socio-economic empowerment after divorce. The study concludes that substantive justice for women victims of domestic violence requires an integrative legal framework that combines responsive legal norms, effective judicial practices, and broader social transformation to ensure comprehensive protection, recovery, and access to justice.